Chapter Determinants of Established Entrepreneurs' Innovative Activity in Northern and Western Europe - Močnik, Dijana (InTechOpen, 2018)
For established entrepreneurs from Western European economies (WEEs) and Northern European economies (NEEs), we estimated relationships between firms' innovative activity and their owner-managers' educational level, the firms' international orientation, and their growth aspirations. International orientation proved to be positively and significantly related to innovative activity in both groups, but associations were stronger in NEEs. Established entrepreneurs with higher educational levels are more innovative than those with less education, with an exception for NEEs, where more innovative are entrepreneurs with a secondary instead of a postsecondary degree. Established entrepreneurs with growth aspirations are more innovative only for the NEEs. The empirical results confirm our two hypotheses for both groups of economies, whereas the third hypothesis which suggests that established entrepreneurs with aspirations for growing their firms are expected to be more innovative is confirmed only for the NEEs.